The Expedition of Franz Wilhelm Junghuhn and the Development of Cinchona as a Commodity in the Dutch East Indies (1835–1896) - Junghun Sylvawana Octoriansyah; Ririn Darini (Yupa: Historical Studies Journal, 2026)
This article examines Franz Wilhelm Junghuhn’s important contribution to the development of cinchona cultivation in the Dutch East Indies, now Indonesia. Junghuhn’s extensive expeditions in Java and Sumatra supported the successful adaptation and cultivation of cinchona, an important antimalarial plant, in the region. This article highlights his innovative methods and analyzes the economic, social, and political impacts of cinchona cultivation on the Dutch East Indies government and local communities. It concludes that Junghuhn’s work not only advanced botanical knowledge but also played a significant role in combating malaria and strengthening the colonial economy through cinchona exports.